Implementation of ISO 9001:2015 and ISPS Code in Access Control Procedures at PT XYZ - Wardana, Wisnu; Rochmoeljati (Jurnal Serambi Engineering, 2026)
This article summarizes an independent internship project conducted at PT XYZ during September–December 2025 within the HSSE (Health, Safety, Security, and Environment) function. The focus was evaluating the implementation of ISO 9001:2015 and the International Ship and Port Facility Security (ISPS) Code in the port facility access control procedure, especially at the main gate and restricted areas. Data were collected through on-site observation, document review of access control SOPs, inspection forms, and risk records (HIRADC), and discussions with security, HSSE, and operational personnel. The analysis applied process mapping, risk-based thinking, HIRADC, and gap analysis to compare field practices with standard requirements. Results indicate that access control is implemented through layered controls: identity and permit verification, RFID-based access restrictions, CCTV monitoring, system logging (e.g., CTOS), and routine inspections. Key risks such as unauthorized access, human error during goods checks, and night-shift fatigue are mitigated by administrative controls, supervision, and shift management. Practical issues were found in reporting format differences and mismatches between field conditions and administrative records, requiring periodic verification and data standardization to strengthen audit readiness and continual improvement.